Unraveling the spatial and signaling dynamics and splicing kinetics of immune infiltration in osteoarthritis synovium - Wang, Chuan; Zeng, Zevar; Wang, Tao; Xie, Zhihong; Zhang, Jian; Dong, Wentao; Zhang, Fei; Peng, Wuxun (Frontiers in Immunology, 2025)
IntroductionOsteoarthritis (OA), a debilitating joint disorder characterized by synovial inflammation and immune myeloid cell infiltration, currently lacks a comprehensive spatial and transcriptional atlas. This study investigates the spatial dynamics, splicing kinetics, and signaling pathways that drive immune infiltration in OA synovium.MethodsWe integrated single-cell RNA sequencing (scRNA-seq) data from 8 OA and 4 healthy synovial samples with spatial transcriptomics using Spatrio. Spatial transition tensor (STT) analysis decoded multistable spatial homeostasis, while splicing kinetics and non-negative matrix factorization (NMF) identified gene modules. CellPhoneDB and pyLIGER mapped ligand-receptor interactions and transcriptional networks.ResultsRe-annotation of scRNA-seq data resolved synovial cells into 27 subclasses. Spatial analysis revealed OA-specific attractors (8 in OA vs. 6 in healthy samples), including immune myeloid (Attractor3) and lymphoid infiltration (Attractor4). Key genes OLR1 (myeloid homeostasis) and CD69 (T-cell activation) exhibited dysregulated splicing kinetics, driving inflammatory pathways. Myeloid-specific transcription factors (SPI1, MAF, NFKB1) and lymphoid-associated BCL11B were identified as regulators. Computational drug prediction nominated ZILEUTON as a potential inhibitor of ALXN5 to mitigate myeloid infiltration.DiscussionThis study delineates the spatial and transcriptional landscape of OA synovium, linking immune cell dynamics to localized inflammation. The identification of OLR1 and CD69 as spatial homeostasis drivers, alongside dysregulated signaling networks, offers novel therapeutic targets. These findings advance strategies to modulate immune infiltration and restore synovial homeostasis in OA.